Detection and characterization of prednisolone metabolites in human urine by LC‐MS/MS. (18th February 2015) - Matabosch, Xavier; Pozo, Oscar J.; Pérez‐Mañá, Clara; Papaseit, Esther; Segura, Jordi; Ventura, Rosa
Abstract : Glucocorticosteroids are prohibited in sports when used by systemic administrations (e.g. oral), whereas they are allowed using other administration ways. Strategies to discriminate between administrations routes have to be developed by doping control laboratories. For this reason, the metabolism of prednisolone (PRED) was studied using liquid chromatography coupled to tandem mass spectrometry. A single oral (10 mg) dose of PRED was administered to two healthy male volunteers. Urine samples were collected up to 6 days after administration. Samples were hydrolyzed with β ‐glucuronidase and subjected to liquid–liquid extraction with ethyl acetate in alkaline conditions. The extracts were analyzed by liquid chromatography coupled to tandem mass spectrometry. Precursor ion scan methods ( m / z 77, 91, 105, 121, 147 and 171) in positive ionization and neutral loss scan methods (76 and 94 Da) in negative ionization modes were applied for the open detection of PRED metabolites. Using these methods, PRED parent compound plus 20 metabolites were detected. PRED and 11 metabolites were characterized by comparison with standards of the compounds (PRED, prednisone, 20 β ‐dihydro‐PRED and 20 α ‐dihydro‐PRED, 20 β ‐dihydro‐prednisone and 20 α ‐dihydro‐prednisone, 6 β ‐hydroxy‐PRED and 6 α ‐hydroxy‐PRED, 20 β isomers and 20 α isomers of 6 β, 11 β, 17 α, 20, 21‐pentahydroxypregnan‐1, 4‐diene‐3‐one, 6 α, 11 β, 17 α, 20 β, 21‐pentahydroxypregnan‐1, 4‐diene‐3‐one and Δ 6 ‐PRED). Using mass spectrometric data, feasible structures were proposed for seven of the remaining nine detected metabolites, including several 6‐hydroxy‐metabolites. Eleven of the characterized metabolites have not been previously described. Maximum excretion rates for PRED metabolites were achieved in first 24 h; however, most of the metabolites were still detectable in the last collected samples (day 6). Copyright © 2015 John Wiley & Sons, Ltd.